Car and truck tire wear particles in road dust samples - A quantitative comparison with traditional microplastic polymer mass loads - Isabel Goßmann; Maurits Halbach; Barbara Scholz-Böttcher (PANGAEA, 2023)
This data set provides quantitative mass loads of tire wear particles (TWP) and traditional microplastics (C-PE, C-PP, C-PS, C-PVC, C-PMMA, C-PET, C-PC, C-MDI-PUR) in the urban environment. A differentiation between car and truck tire wear (CTT and TTT) was presented. The C-PVC cluster might be interfered by additional anthropogenic sources, as the C-PVC indicator naphthalene is highly unspecific, accordingly the given results primarily reflect the order of magnitude. In this study, road dusts were analyzed and measured with pyrolysis-gas chromatography-mass spectronomy (Py-GC/MS). Pyrolysis was performed at 590°C in a micro-furnace pyrolizer (EGA/Py-3030D, FrontierLabs) connected to an auto-shot sampler (AS-1020E, FrontierLabs). A gas chromatograph (6890 N, Agilent) equipped with a DB-5MS column was used for separation. The mass spectrometer (MSD 5973, Agilent) operated with full-scan mode. A gas chromatograph (6890 N, Agilent) equipped with a DB-5MS column was used for separation. The mass spectrometer (MSD 5977A) operated with full-scan mode. Additional information are found in the supplementary information of the related study. Road dust samples were collected in a mid-sized German city (Oldenburg). Road dust were contaminated with traditional microplastics and tire wear particles. The here presented data are part of a study, which has been published in February 2021 (doi: 10.1016/j.scitotenv.2021.145667).